Representative Pores: An Efficient Method to Characterize Activated Carbons - de Oliveira, Jose Carlos Alexandre; Galdino, Ana Luisa; Gonçalves, Daniel V; Silvino, Pedro F. G.; Cavalcante, Celio L.; Bastos-Neto, Moises; Azevedo, Diana C.S.; Lucena, Sebastiao M. P. (Frontiers in Chemistry, 2021)
We propose a pore size analysis methodology for carbonaceous materials that reduces complexity while maintaining the significant elements of the structure-property relationship. This method chooses a limited number of representative pores, which will constitute a simplified kernel to describe the pore size distribution (PSD) of an activated carbon. In this study we use the representative pore sizes of 7.0, 8.9, 18.5, and 27.9 Å and N2 isotherms at 77.4 K to determine the PSD which is later applied to predict the adsorption equilibrium of other gases. In this study we demonstrate the ability to predict adsorption of different gas molecules on activated carbon from the PSD generated with representative pores (PSDrep). The methodology allows quick solutions for large-scale calculations for carbonaceous materials screening, in addition to make accessible an easily understood and prompt evaluation of the structure-property relationship of activated carbons. In addition to the details of the methodology already tested in different fields of application of carbonaceous materials, we present a new application related to the removal of organic contaminants in dilute aqueous solutions.